The correlation between learning approach and learning achievement among medical education students - Fransiska Roslinda Dua Neang; I Made Artawan; Rahel Rara Woda; Desi Indriani Rini (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This research’s objective is to find the link between learning approach and learning achievement of medical education students at the Faculty of Medicine, University of Nusa Cendana Kupang. This research is an analytical observational research with cross-sectional design that was conducted on medical education students of Faculty of Medicine, University of Nusa Cendana Kupang. Sample was obtained by proportionate stratified random sampling technique. Data was obtained using Revised Study Process Questionnaire 2-Factors (R-SPQ2F) on 160 respondent who met the inclusion criteria. Sample was analyzed bivariately using coefficient contingency statistical test. From the 160 respondents, data shows that the number of students who used the deep approach learning approach is 139 (86,9%) students, number of students who used the surface approach is 21 (13,1%) students. For the various category of learning achievements that the students acquire is commendation category with the total of 121 (75,6%) students, very satisfying category with the total of 39 (24,4%) students, satisfying category with the total of 0 students. Bivariate analysis shows results of p value = 0,631 and r value = 0,038.